ANALISIS PENGARUH AUDIT TENURE, STRUKTUR CORPORATE GOVERNANCE, DAN UKURAN KANTOR AKUNTAN PUBLIK (KAP) TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Kasus Perusahaan Manufaktur yang Terdaftar di BEI Periode 2018-2020) - Laila Nur Rosyidah; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the effect of audit tenure, corporate governance structure, and the size of a public accounting firm (KAP) on the integrity of financial statements, the population in this study are manufacturing companies listed on the Indonesian stock exchange for the 2018-2020 period as many as 193 companies with a sample determination using purposive sampling technique in order to obtain 35 samples. This type of research is using quantitative methods, classified as the type of correlational research. The data used is secondary data with the type of documentation data. The data analysis method used is logistic regression analysis, descriptive statistics, multicollinearity test, test assessing the whole model, test the coefficient of determination, and test the feasibility of the regression model.The results of the study partially audit tenure variables have no significant effect on the integrity of financial statements, the corporate governance structure variable: managerial ownership has no significant effect on the integrity of financial reports, institutional ownership has no significant effect on the integrity of financial statements, the audit committee has a significant positive effect on the integrity of financial statements, and the variable of KAP size has a significant positive effect on the integrity of financial statements.Keywords: audit tenure, corporate governance structure, and size of public accounting firm.